Beginning Java Web development : an introduction to lightweight development, deployment, and security - Kalin, Martin; Safari eBooks ([Place of publication not identified] : O'Reilly, 2016)
"Get practical experience in professional Java web programming for enterprises. Start by learning about web apps and databases using JavaServer Pages (JSP) and Plain Old Java Objects (POJOs). As you progress, you'll learn how to extend and improve upon a sample shopping cart web application. Finally, you'll spin up an Apache Tomcat web server and see how it all comes together."--Resource description page.
Title from resource description page (Safari, viewed September 9, 2016).
Presenter, Martin Kalin.
Keywords: Java (Computer program language); Web site development; Electronic books